2011
DOI: 10.4028/www.scientific.net/amr.287-290.1015
|View full text |Cite
|
Sign up to set email alerts
|

Study on Strength and Durability of Concrete Containing Recycled Coarse Aggregate Manufactured with Various Method

Abstract: This paper presents the results of experimental study on the effects of adhered mortar content on strengths and durability of concrete. Compressive, tensile and shear strengths, modulus of elasticity, drying shrinkage and carbonation were tested on concrete mixtures with the water cement ratio of 0.43, 0.50 and 0.60 using 3 kinds recycled coarse aggregate and a riversand. The test results of concrete indicated higher compressive, tensile amd shear strengths and higher modulus of elasticity for concrete using r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…However, the use of recycled aggregate is allowed in specific amounts in some standards [8]. On the other hand, in case of service life and durability, there are some studies that showed these properties of concrete with recycled aggregate are not as good as those of conventional concrete [12,13] while others concluded that concrete with recycled aggregate has better durability than conventional concrete [14]. While there is no commercial approach for the use of high-quality recycled aggregate, the consumers can still be motivated to use more of recycled aggregate upon the availability of more data.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of recycled aggregate is allowed in specific amounts in some standards [8]. On the other hand, in case of service life and durability, there are some studies that showed these properties of concrete with recycled aggregate are not as good as those of conventional concrete [12,13] while others concluded that concrete with recycled aggregate has better durability than conventional concrete [14]. While there is no commercial approach for the use of high-quality recycled aggregate, the consumers can still be motivated to use more of recycled aggregate upon the availability of more data.…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly believed that RA has high porosity, low apparent density, and high water adsorption, as the normally used mechanical process of RA from blocks of demolished concrete into relatively small grains, may cause RA suffer internal damage such as micro-cracks [1][2][3] and RAC have relatively low strength [7]. Some investigations found that a couple of approaches such as particle shaping and heating plus grinding, can considerably improve the quality of RA, in the forms of enhanced density and lowered crushing value of RA, and hence improve mechanical strength of RAC [8][9][10]. However, there is a lack of literature on the characteristics of flaws in RA and the influence of the flaws in RA on fracture behavior of RAC.…”
Section: Introductionmentioning
confidence: 99%